(untitled) (Journal Intellectual Sufism Research (JISR), 2024)
According to Ibn Kathir and Ibn Taymiyyah, Tafsir bi al-Ma’thur is the method of interpretation that is closest to the truth and is more obligatory to follow. This is because Tafsir bi al-Ma’thur distances interpretation from personal thought and uses narratives from the Prophet, Companions, or Tabi’in as its reference sources. This research employs a descriptive-analytical approach, including library research, with data sourced from literature-based references, as well as verifiable research, to re-examine the principles and methods of interpretation that have developed in relation to contemporary relevance. In this context, Tafsir bi al-Ma’thur, which is considered the closest to the truth, actually contains Israiliyyat narratives that should be a focus for further study.